Root exudate monosaccharides modulate the pathogenicity of Ralstonia pseudosolanacearum - Fang, Keli; Zhang, Dongdong; Zhang, Benqiang; Li, Xikun; Zhang, Yang (Frontiers in Microbiology, 2026)
The Ralstonia solanacearum species complex (RSSC) is a devastating soil-borne pathogen that causes bacterial wilt in solanaceous crops. However, the response of RSSC to monosaccharides—key components of root exudates released into the rhizosphere—remains unclear. We supplemented culture media with several typical monosaccharides derived from tobacco root exudates to mimic rhizosphere signals and examined their effect on the expression of bacterial virulence factors. Transcriptome analysis revealed that galactose markedly altered the physiological status of RSSC, inducing a state resembling that during plant infection. Among the monosaccharides tested, galactose specifically up-regulated the expression of type III secreted effectors. Notably, galactose also actively induced nitrogen metabolism, leading to the production of nitrous oxide and other reactive nitrogen species, which may, like reactive oxygen species, enhance pathogenicity. Furthermore, metabolites extracted from galactose-induced RSSC cultures triggered cell death when infiltrated into tobacco leaves.